Analisis Dan Evaluasi Peraturan Perundang-Undangan Tentang MINERBA Di Kawasan Hutan Lindung - Dr. Tri Hayati, S.H., M. H (PBHN, 2015)
Analisis Dan Evaluasi Peraturan Perundang-Undangan Tentang MINERBA Di Kawasan Hutan Lindung